Taneyan Lanjhang: Spatial Practice and the Formation of Sakinah Family in Madurese Society - Muchlis muchlis; Achmad Gunaryo; Imam Yahya; Ridan Muhtadi; Achmad Komaruddin (IAIN Palangka Raya, 2026)
Existing studies on Islamic family life and family resilience have predominantly focused on normative-religious frameworks or individual family dynamics, while limited attention has been given to traditional settlement systems as socio-cultural structures shaping everyday family practices. The study aimed to analyse how the Taneyan Lanjhang system structures family interactions, organizes kinship relations, and contributes to the formation of harmonious family life in Madurese society. Using a qualitative approach with a focused family ethnography design, this research involved 15 informants from five extended families residing within one Taneyan Lanjhang complex in Madura. Data were collected through semi-structured interviews, participant observation, and socio-cultural documentation. Moreover, data were analysed using reflexive thematic analysis. The findings indicate that Taneyan Lanjhang functions not only as a residential arrangement but also as a kinship-based social system that regulates intergenerational interaction, moral authority, collective responsibility, and religious practices within family life. The spatial proximity of households and communal spaces, along with the role of elders, contributes to mechanisms of conflict mediation, social control, emotional support, and resource sharing among family members. At the same time, the study also identifies tensions within the system, including limited privacy and the persistence of hierarchical authority in family relations. This study presents Taneyan Lanjhang as a socio-cultural and spatial framework through which family harmony and collective resilience are negotiated and maintained in the everyday lives of Madurese Muslim communities.